2020
DOI: 10.2147/ijnrd.s198222
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluating Nephrocheck<sup>®</sup> as a Predictive Tool for Acute Kidney Injury</p>

Abstract: Acute kidney injury (AKI) is a common complication in critically ill patients in the intensive settings with increased risks of short-and long-term complications and mortality. AKI is also associated with an increased length of stay in intensive care units (ICU) and worse kidney function recovery at hospital discharge. The management of AKI is one of the major challenges for nephrologists and intensivists overall for its early diagnosis. The current KDIGO criteria used to define AKI include the serum creatinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 67 publications
(75 reference statements)
0
22
0
1
Order By: Relevance
“…Moreover, similarly to NGAL, [IGFBP-7] × [TIMP-2] is now available in the form of a point-of-care test, Nephrocheck. Nalesso et al [ 23 ] have analyzed the usefulness of Nephrocheck based on the literature analysis. The authors concluded that the use of this test should be considered in the case of any large surgery or when invasive procedure is planned.…”
Section: Markers Of Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, similarly to NGAL, [IGFBP-7] × [TIMP-2] is now available in the form of a point-of-care test, Nephrocheck. Nalesso et al [ 23 ] have analyzed the usefulness of Nephrocheck based on the literature analysis. The authors concluded that the use of this test should be considered in the case of any large surgery or when invasive procedure is planned.…”
Section: Markers Of Injurymentioning
confidence: 99%
“…The major restriction is the fact that the predictive value of [IGFBP-7] × [TIMP-2] product increases with the severity of patient condition. In practice, the marker distinguishes quite precisely between those who develop severe AKI and no AKI, but copes rather poorly with the prediction of mild forms of AKI [ 23 ].…”
Section: Markers Of Injurymentioning
confidence: 99%
“…Urinary [TIMP-2] and [IGFBP7] are two markers of renal tubule injury involved in G1 cell cycle arrest. These two newer stress and damage biomarkers have shown good performance for the early detection of AKI [6]. Due to their strong performance, we used these biomarkers to screen sepsis patients to determine which patients were at a high risk for AKI and needed bundled care.…”
Section: Introductionmentioning
confidence: 99%
“…With this publication, Tavares et al stimulate new investigations on the subject to be done with NGAL, KIM-1 and the other molecules. Second generation biomarkers, TIMP-2 and IGFBP-7, 7 which reflect the cell-cycle interruption of cells in the proximal and distal tubular epithelium, will probably be tested. Some of them detect cell insults, 7 , 8 including sublethal ones, from clinical or surgical stress, even in the first 12 hours, as they are also used to identify the persistence of AKI epithelial lesion in AKIN 2 and 3 stages.…”
mentioning
confidence: 99%
“…Second generation biomarkers, TIMP-2 and IGFBP-7, 7 which reflect the cell-cycle interruption of cells in the proximal and distal tubular epithelium, will probably be tested. Some of them detect cell insults, 7 , 8 including sublethal ones, from clinical or surgical stress, even in the first 12 hours, as they are also used to identify the persistence of AKI epithelial lesion in AKIN 2 and 3 stages. 9 The promising expectation is that, in the near future, these biomarkers will consolidate as tools for risk stratification and severity in AKI, as well as for the definition of personalized clinical procedures, including in glomerulopathies.…”
mentioning
confidence: 99%